SPATIAL-TEMPORAL ANALYSIS OF THE INCIDENCE OF CHRONIC DISEASES AND THEIR IMPACT ON HEALTH EXPENDITURE IN POLAND - Budny, Dawid Rafał (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
According to the World Health Organization, chronic diseases are a growing cause of death in the world. Due to their long-term nature, they generate high medical private and public costs. For this reason, performing analysis of spatial differentiation of the dynamics of morbidity is the key element of effective management of the health sector and implementation of health policy. The purpose of this article is spatial-temporal analysis of the incidence of chronic diseases and their impact on health spending in Poland by province. The study used the tools of geographic information systems and the exploratory analysis of the spatial data. The study mainly focuses on the characteristics of variables: morbidity, health expenditure and budgets of households by province. The test was performed on the basis of statistical data, the report on “The health situation of the Polish population and its determinants” published by the National Institute of Hygiene in the period 2008-2012. The results would be found use full to assess the spatial-temporal distribution of the incidence of chronic diseases and their impact on health expenditure.